Evakkoreissu Ruotsiin:muistamisen arvoiset kokemukset ja tapahtumat - Hautala-Hirvioja, Tuija Helena (2016)
Tuija Hautala-Hirvioja: Evakkoreissu Ruotsiin – muistamisen arvoiset kokemukset ja tapahtumat Summary: Evacuation to Sweden – the experiences and events worth remembering My article deals with experiences of people who were evacuated from the area of Rovaniemi in Lapland to Sweden for the years 1944–1945. The material consists of fifteen interviews, which Ritva Tuomaala did while working as a doctor at a rehabilitation hospital (Rovaniemen Veljessairaala) in Rovaniemi in 1991–2000, three temporary reminiscences written during an evacuation journey or straight after it, and five publications based on reminiscences collected later. The material is quite diversified. The interviews were done during rehabilitation periods, so they have been salutary and therapeutic in nature. The contemporary reminiscences describe events and do not include interpretations yet. Instead, publications of the reminiscence material include analysing and reflecting the relation between the past and present as well as interpretation related to the moment of reminiscing. The Moscow Armistice signed on 19 September 1944 was one reason for the Lapland War between the former brothers-in-arms, the Finns and the Germans. There was a fear of the civil population getting stuck in the way of potential fighting. 103 885 people were evacuated from Lapland: 56 417 of them were transferred to Sweden and the rest to Ostrobothnia. People were allowed to take some food, valuables and clothes for the evacuation journey – only as much as one could carry. Of animals, only horses and cows were evacuated. The journey was hard not only physically but also mentally. Evacuees did not know about the future, and beliefs and rumours easily turned into reality. In Haparanda, evacuees were welcomed kindly and depending on what village they came from, guided to different big tents. After that, all comers were registered, and they got emergency visas. From Haparanda, evacuees were transferred to the parish villages of Norrbotten and Västerbotten. The Lapland War caused ...